An evidence-based approach to specifying survey effort in ecological assessments of bat activity. (March 2019) - Richardson, Suzanne M.; Lintott, Paul R.; Hosken, David J.; Mathews, Fiona
Abstract: Robust ecological assessments are fundamental for effective wildlife conservation. Owing to the high legal protection of bats, surveys are frequently required as part of ecological assessments. Yet there is uncertainty about the amount of survey effort that should be deployed to facilitate bat protection. Bat activity can be extremely variable, and capturing periods of high activity can be as important as estimating parameters such as the median activity level. However the frequency and intensity of surveys required to capture the required information is unknown. Here we assessed the probability that acoustic surveys of differing durations would detect periods of high activity within a focal site and the importance of a site relative to others in a regional or national context. We randomly subsampled from 660 nights of activity data collected from 33 wind farm sites across Britain. The minimum surveying effort required to classify bat activity accurately varied between species and was dependent on weather conditions. We found that the survey periods required to give reasonable certainty in assessing risk exceeded those currently recommended in Europe. The approach of using bat activity accumulation curves, as described here, is transferrable to other situations where determining surveying effort and risk is necessary to ensure that ecological assessments provide a robust evidence base, whilst minimising the time and expense of surveys.